Modulating photoelectrochemical water splitting performance by constructing a type-II heterojunction between g-C3N4 and BiOI. (15th January 2021) - Vinoth, S.; Rajaitha, P. Mary; Pandikumar, A.
Abstract : g-C3 N4 /BiOI type-II heterojunction prepared by ultrasonically aided hydrothermal method exhibits high stability during PEC water splitting for up to 6000 s at 1.23 V vs. RHE. Abstract : In this work, a type-II heterojunction was constructed between g-C3 N4 and BiOI by ultrasonically assisted hydrothermal synthesis for photoelectrochemical water splitting. The g-C3 N4 was decorated on BiOI microspheres with a well-defined heterostructure, which reduced the charge recombination process, consistent with the data from photoluminescence (PL) and electrochemical impedance spectroscopy (EIS). The g-C3 N4 /BiOI hybrid material exhibits enhanced photocurrent density, ∼13-fold higher than that of g-C3 N4 and ∼2 fold higher than pristine BiOI. Furthermore, high stability was achieved for the g-C3 N4 /BiOI hybrid material with 6 wt% g-C3 N4 for up to 6000 s at 1.23 V vs. RHE, and the photo-conversion efficiency reached 14-fold higher than that of g-C3 N4 and 1.6 times higher than that of BiOI microspheres. The high photoelectrocatalytic performance achieved by the 6% g-C3 N4 /BiOI material was attributed to the formation of type-II heterojunction between the g-C3 N4 and BiOI interfaces that could facilitate the photoinduced charge separation–migration and thereby minimize the charge recombination process.